Vibration suppression and coupled interaction study in milling of thin wall casings in the presence of tuned mass dampers - Kolluru, Kiran V.; Axinte, Dragos A.; Raffles, Mark H.; Becker, Adib A. (SAGE, 2014)
Damping of machining vibrations in thin-wall structures is an important area of research due to the ever-increasing use of lightweight structures such as jet engine casings. Published literature has focussed on passive/active damping solutions for open geometry structure (e.g. cantilever thin wall), whereas more challenging situations such as closed geometry structures (e.g. thin wall ring-type casings) were not taken into consideration. In this study, a passive damping solution in the form of tuned viscoelastic dampers is studied to minimise the vibration of thin wall casings while focussing on the change in coupled interaction between tool and workpiece due to added tuned dampers. Finite element simulation was carried out to evaluate the effectiveness of tuned dampers in single impact excitation, and this was further validated experimentally through modal impact testing. A reduction in root mean square value, with tuned dampers, of about 2.5 and 4 times is noted at higher and lower depths of cut, respectively, indicating a moderate dependency on depth of cut. A change in coupled interaction of workpiece with tool’s torsional mode (in undamped state) to that of tool’s bending mode (with tuned dampers) was also noted. Variation in machined wall thickness of the order of 6 mm is noted due to the change in coupled interaction from torsional mode to bending mode of tool.